Exercise testing for primary care and sports medicine physicians - Evans, Corey H. (Springer New York, 2009)
This practical book is a guide to the exercise stress test performed to determine a patient’s risk of developing coronary heart disease. Edited by Drs. Corey H. Evans and Russell D. White, the text is ideal for primary care, family medicine and sports medicine physicians, sports physiologists and trainers. Sections are devoted to performing the exercise stress test, test interpretation and application, and sports medicine applications. Additionally, common abnormal responses and risk stratification of symptomatic and asymptomatic patients are detailed, and flow charts and algorithms bolster the decision-making process. With its straightforward presentation of key material, this text is a welcome resource for those caring for athletes and patients at risk for heart disease. Performing the exercise test - Exercise physiology for graded exercise testing: a primer for the primary care clinician - Performance of the exercise test - Exercise testing special protocols - Testing special populations - Interpretation and application of the exercise test - Interpreting the exercise test - Common abnormal responses seen with exercise testing and how to manage them - Nuclear imaging with exercise testing - Stress echocardiography - Stratifying symptomatic patients using the exercise test and other tools - Exercise testing as applied to the preoperative patient - Exercise testing and other tools for risk stratification in~asymptomatic patients - Promoting therapeutic lifestyle change and the primary prevention of coronary artery disease - Exercise testing after bypass or percutaneous coronary intervention - Legal aspects of graded exercise testing - Sports medicine applications of exercise testing - Measuring physical fitness - Generating an exercise prescription from the exercise test - The role of gas analysis and cardiopulmonary exercise testing - Testing athletic populations - Exercise testing for the symptomatic athlete - Case studies - Case studies: lessons learned from~interesting cases.